PENGARUH PEMAKAIAN ALAT PENGHEMAT BAHAN BAKAR POWER X TERHADAP PERFORMANCE MOTOR DIESEL - -, Sudarsono (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2004)
The performance of combustion engine of torak can be seen from torque, break power, , the break mean effective pressure, fuel consumption, specific fuel consumption, AFR and efficiency produced. The research discusses the effect of fuel saving consumption â€œPower Xâ€ to the performance of diesel motor. The research used speed average such as 1600, 1950, 2300, 2650, 3000 Rpm. The result showed that the use of Power X caused torque increased 3,160782 Nm or 2,72%, power increased 0,7613 kW or 2,74%, effective pressure increased 18,3622 kPa or 2.73%. Fuel consumption decreased 0,3572 gr/second or 14,34 %, specific fuel consumption decreased 0,01516 mg/joule or 16,83%. Ratio between air and fuel increased 1,8476 or 14,67%. Thermal efficiency increased 0,05102 or 20,19 %.